THE PECULIARITIES OF SOIL BIOTA DEVELOPMENT IN HEMP SOWN AREAS UNDER ORGANIC FARMING TECHNOLOGIES AND ITS IMPACT ON THE PRODUCTIVITY - Piskovyі, М. B.; Pylypchenko, A. V. (Scientific Progress & Innovations, 2019)
In any agricultural production when there is a change in the kind of activity or in cultivation technologies the number of issues arise that lead to huge financial and environmental losses or can even put an end to the production. After the group of “Arnika” companies set a strategic goal to transfer all agricultural produc-tion to the technologies of organic farming, it faced a number of challenges, one of which is the stabilization of cultivated areas’ productivity by improving soil biological activity, and namely, intensifying the function-ing of soil zoo-biota and microbial cenosis. Provided that the absence of applying mineral fertilizers will lead to decreasing soil fertility in organic farming, it is necessary to develop the elements of technology, which would enable the activation of functioning soil zoo-biota and microbial cenosis besides providing hemp with macro and microelements, organic fertilizers and green manure crops,. In comparison with the classical technology of hemp cultivation the organic system eliminates stressful situations (the effect of min-eral fertilizers and means of plant protection) on the one hand, but on the other hand, the increase of the number of cultivations improves soil air balance, which contributes to the propagation and development of soil biota. The research, conducted at the enterprises of the group of “Arnika” companies in the town of Hlobyne, Poltava region, began in 2015. The obtained experimental data enabled to make changes in the elements of hemp organic cultivation technologies and thus to stabilize the quantitative composition of earthworms, ticks, Podura springtails, and microbial cenosis. The results are presented in the article as to investigating quantitative, qualitative composition and the activity of biodiversity functioning of the natural and agricultural soil eco systems while sown hemp cultivation according to the technologies of organic farming. It was established by the research that despite high adaptability of soil biota to constant environ-mental changes, the balance of soil cenosis is disrupted by anthropogenic influence. The using of organic farming technologies enables soil zoo-biota and micro-flora to avoid stressful loadings as a result of mineral fertilizers and plant protection means’ influence. At the same time the studies of changing sown hemp productivity during the transition from classical cultivation technology to organic farming system shows that there are some peculiarities, which should be revealed in the process of further research.